The Burkholderia cepacia complex as a microbial determinant of complicated cystic fibrosis: pathogenetic links and clinical aspects (systematic review of the literature) - Martsev , Maksym; Pashkova , Iuliia (The Ukrainian Scientific Medical Youth Journal, 2025)
cystic fibrosis is an autosomal recessive disease that disrupts the exocrine secretion of the human body. Its occurrence is caused by a mutation in the CFTR gene. Despite the relentless progress in the development of effective treatments for the disease over the past 40 years, mortality from cystic fibrosis is largely due to chronic colonization of patients' bodies by certain types of bacteria: Pseudomonas aeruginosa, methicillin-resistant Staphylococcus aureus (MRSA), Haemophilus influenzae, Stenotrophomonas maltophilia, Achromobacter xylosoxidans, and species of the Burkholderia cepacia complex (BCC). The Burkholderia genus remains largely unexplored, as only last year 130 species of β-proteobacteria were discovered. More than 22 species are capable of provoking complications of cystic fibrosis and can cause the "B. cepacia syndrome" even in patients who do not have cystic fibrosis but have immunodeficiency states. Over 40 sources were reviewed, taken from scientific databases such as PubMed, MEDLINE, Embase, Google Scholar, Scopus, and the American Society for Microbiology. It was analyzed and established that the Burkholderia cepacia complex plays a significant role in complicating cystic fibrosis as an independent genetically determined disease. This is evidenced by a decrease in one-year survival by more than 10% in patients after lung transplantation, as well as the fact that contamination of cystic fibrosis patients' bodies with Burkholderia cenocepacia is a contraindication for lung transplantation. It has been established that the risk of contamination by this group of bacteria is very high, as the described microorganisms have an extremely wide distribution worldwide. Certain medical equipment and therapeutic agents remain contaminated as well. The high virulence and antibiotic resistance of this family of bacteria pose a socially dangerous factor. The obtained data serve as an excellent basis for the development of various therapeutic methods, namely: antibiotic therapy with new drugs, effective combinations of antibacterial agents, the use of bacteriophages, and the creation of vaccines against BCC. The prospect for further research remains the issue of treating complications caused by BCC.